Prevalence, causes, and consequences of moral distress in healthcare providers caring for people living with dementia in long-term care during a pandemic - Lynn Haslam-Larmer; Alisa Grigorovich; Hannah Quirt; Katia Engel; Steven Stewart; Kevin Rodrigues; Pia Kontos; Arlene Astell; Josephine McMurray; AnneMarie Levy; Kathleen S Bingham; Alastair J Flint; et al. (SAGE Journals, 2022)
Healthcare providers caring for people living with dementia may experience moral distress when faced with ethically challenging situations, such as the inability to provide care that is consistent with their values. The COVID-19 pandemic produced conditions in long-term care homes (hereafter referred to as ‘care homes’) that could potentially contribute to moral distress. We conducted an online survey to examine changes in moral distress during the pandemic, its contributing factors and correlates, and its impact on the well-being of care home staff. Survey participants (n = 227) working in care homes across Ontario, Canada were recruited through provincial care home organizations. Using a Bayesian approach, we examined the association between moral distress and staff demographics and roles, and characteristics of the long-term care home. We performed a qualitative analysis of the survey’s free-text responses. More than 80% of care home healthcare providers working with people with dementia reported an increase in moral distress since the start of the pandemic. There was no difference in the severity of distress by age, sex, role, or years of experience. The most common factors associated with moral distress were lack of activities and family visits, insufficient staffing and high turnover, and having to follow policies and procedures that were perceived to harm residents with dementia. At least two-thirds of respondents reported feelings of physical exhaustion, sadness/anxiety, frustration, powerlessness, and guilt due to the moral distress experienced during the pandemic. Respondents working in not-for-profit or municipal homes reported less sadness/anxiety and feelings of not wanting to go to work than those in for-profit homes. Front-line staff were more likely to report not wanting to work than those in management or administrative positions. Overall, we found that increases in moral distress during the pandemic negatively affected the well-being of healthcare providers in care homes, with preliminary evidence suggesting that individual and systemic factors may intensify the negative effect.
Keywords: 111708 Health and Community Services; 111099 Nursing not elsewhere classified; 110308 Geriatrics and Gerontology; 160512 Social Policy